Images of the Holy Trinity: Origins, Iconographis Features, Deformations - Maslauskaitė, Sigita (Religija ir kultūra, 2012)
The history of the image of the Holy Trinity reveals that the interpretation of this Christian mystery posed and still poses a challenge Christianity has attempted to face during general meetings encouraging the publishing of theological tracts and enlightening artists as well as those who commission works of art. Meanwhile, artists have tried to depict the glory of one God in three persons, distorting the image to a greater or lesser degree. Christian images often attributed human qualities to the Trinity of God and bestowed Him with an anthropomorphic silhouette. Some of them went so far as to portray the three-faced Trinity revealing a three-theistic thinking, which was a complete diversion from searching for the image of God in three persons. However, in the Christian iconographic tradition it would have been an absurd thing to do. On the contrary, the majority of the images of the Holy Trinity are worthy of respect even though they do pose a problem that needs to be faced. The doctrine of incarnation enables the portrayal of the face of God the Son. In the Old Testament, God does not disclose His face, whereas in the New Testament He reveals the face of the eternal Incarnate Word, i.e. Jesus Christ. The Church permitted the depiction of both the human form of Christ and His biographic events. Around 730, John of Damascus quoted Basilius the Great and emphasized that image worshipping was not a pagan cult as it was not the matter that was being celebrated but rather that which was being depicted, thus “we honour not the sacred image, but the prototype of which the artistic object is only a reflection.” Subsequently, the latter phrase comprised the base of all defenders of Christian images and was often being repeated in order to prove that the cult of images was based on the worshipping of the depicted persons but not the depictions themselves. Christians followed the conviction that the Son was the consubstantial image of the prototype and that only the Son “is the image of the invisible God” (Col. 1:15) and “the expressed image of his person” (Heb. 1:3). Thus, the Holy Spirit, in its turn, is also the image of the Son: “and no one can say “Jesus is Lord,” except the Holy Spirit” (1 Cor. 12:3). It is only through the Holy Spirit that we know the Son of God, God the Christ, and see the Father in the Son. By nature, the Word is the proclaimer of the thought, whereas the Spirit is the revealer of the Word. Therefore, only the Son is the living, true and everlasting image of the invisible God containing the Father in Himself, absolutely identical to the Father and only differing in that He has a cause. However, the christomorphic position has not always been gratifying, and it is sometimes thought that Latin Christianity went too far by depicting God humanly. According to French sociologists, such “human, all too human” (Nietzsche) images of God might have contributed to “discrediting” the very idea of God or even the “exculturation” of Christianity. Contemporary art has also been unable to find the means of depicting the Holy Trinity in such a way that both believers and non-believers would not consider it to be provocative. The problem will never be solved if all traditions, doctrines and disciplines, principles and facts, successes and failures in the field are not accepted. The article considers only some of the interpretation aspects of the mystery of the Holy Trinity. The portrayal of the glory of God in three persons, iconographic interpretations and deformations have revealed that throughout the history of Christianity much effort has been made to express “clearly” the essence of the Holy Trinity, and yet the mystery has remained both a mystery and a challenge. As the result, the iconographic history of the Holy Trinity and all the related controversies allow us to reconsider the ontological status of its artistic image.